2021
DOI: 10.1007/s00285-021-01560-y
|View full text |Cite
|
Sign up to set email alerts
|

Unbounded solutions of models for glycolysis

Abstract: The Selkov oscillator, a simple description of glycolysis, is a system of two ordinary differential equations with mass action kinetics. In previous work the authors established several properties of the solutions of this system. In the present paper we extend this to prove that this system has solutions which diverge to infinity in an oscillatory manner at late times. This is done with the help of a Poincaré compactification of the system and a shooting argument. This system was originally derived from anothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A significant number of papers have been devoted to the theoretical and experimental study of oscillations in glycolysis [ 26 , 27 , 28 , 29 , 30 ]. However, the possibility of oscillations in human erythrocyte glycolysis, caused by the modulation of the GAPDH reaction rate by [NAD], has not been reported so far to our knowledge.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant number of papers have been devoted to the theoretical and experimental study of oscillations in glycolysis [ 26 , 27 , 28 , 29 , 30 ]. However, the possibility of oscillations in human erythrocyte glycolysis, caused by the modulation of the GAPDH reaction rate by [NAD], has not been reported so far to our knowledge.…”
Section: Resultsmentioning
confidence: 99%
“…a DPGM = 3892 mM/h, K 1 DPGM = 0.04 mM, K 2 DPGM = 0.013 mM Diphosphoglycerate phosphatase [22] V Na + /K + -ATPase [22] V NaKATP = a NaKATP Na + [ATP] a NaKATP = 0.045 mM/h, Na + = 10 mM [30] All other ATPases are presented by the following equation [22] V ATP = a ATP…”
Section: Mathematical Modelmentioning
confidence: 99%
“…Again, h denotes the interval length. In Table 4, we give the errors produced by the use of Taylor method and in We have shown that the Extended Picard reinforced with segmentary integration gives an excellent approximation to solutions of a strongly non-linear ordinary system such as (33). Same can be said for the Mathieu equation as an inspection of Table 2.…”
Section: Quintic Duffing Equationmentioning
confidence: 98%
“…We remark again that even though this procedure is computationally costly, it pays off by offering a control strategy that is robust to a number of possible (and highly likely) scenarios, by taking into account the uncertainty on parameter estimates [ 29 ].…”
Section: Optimised Mobility Values Based On Uncertaintymentioning
confidence: 99%